PENENTUAN DEWASA AYU DALAM UPACARA PAWIWAHAN MENURUT LONTAR PANCA KANDA DI DESA DARMASABA - Sukmawati, Ni Wayan; I Nyoman Subagia; I Made Dwitayasa (Pangkaja: Jurnal Agama Hindu, 2026)
The determination of dewasa ayu (auspicious day) in Hindu marriage ceremonies according to the Lontar Panca Kanda is not merely a tradition, but a manifestation of spiritual teachings that emphasize the importance of human harmony with the cosmic order. By selecting a time that is astrologically and spiritually appropriate, Hindus believe that marriage will receive divine blessings, harmony, and happiness, and become part of a sacred journey toward a higher purpose in life. Many young couples may not be particularly concerned with tradition or may not fully understand the importance of choosing a traditional lunar month. They tend to prefer a time that aligns with their personal schedules and preferences. The younger generation may have different views on tradition and are more inclined to prioritize practical and personal aspects in planning a wedding. Nevertheless, determining dewasa ayu is crucial before conducting a wedding ceremony. The aims of this study are to analyze why determining dewasa ayu is important in Hindu wedding ceremonies, how dewasa ayu is determined, and what theological meanings are embodied in the determination of dewasa ayu for those performing the ceremony. The research methods used include observation, interviews, and literature study. The results show that the Lontar Panca Kanda serves as one of the main guidelines for determining dewasa ayu, as it contains the principles of wariga (Balinese astrological calendar) and cosmic balance. A good day is chosen not merely because it is free from obstacles, but when cosmic and spiritual constellations are in harmony. This makes the wedding ceremony a form of human participation in the sacred cosmic order. The selection of an auspicious day involves meticulous astrological calculations including the positions of planets, lunar phases, weekdays, astrological combinations, and the compatibility of both partners' horoscopes. All of this is intended to ensure that the marriage begins under the most favorable cosmic energy, thereby minimizing the risk of disharmony and enhancing good fortune and harmony in the household.